2009
DOI: 10.1017/s0047279408002870
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the Implementation of an Integrated National Alcohol Policy in Ireland: Nannies, Neo-Liberals and Joined-Up Government

Abstract: This article explores how proponents of a public health model of alcohol policy have, for more than a quarter of a century, argued consistently but unsuccessfully for an integrated national alcohol policy in the Republic of Ireland. It looks in particular at the past decade, a time when increases in alcohol consumption and related problems strengthened the case for such an integrated policy, and when managerial innovations in the sphere of cross-cutting management appeared to provide a template for its impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
0
37
1
Order By: Relevance
“…However, since then, the government has moved very slowly on the Bill, pressurised by the drinks industry lobby and many political officials opposed to public health legislation [31]. This has been a recurring pattern in recent decades, as Ireland’s neoliberal political and economic establishment has successfully resisted the implementation of public health legislation [32,33,34,35,36]. Indeed, only in 2015 was the Bill’s general scheme finally published, but it may never be enacted [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, since then, the government has moved very slowly on the Bill, pressurised by the drinks industry lobby and many political officials opposed to public health legislation [31]. This has been a recurring pattern in recent decades, as Ireland’s neoliberal political and economic establishment has successfully resisted the implementation of public health legislation [32,33,34,35,36]. Indeed, only in 2015 was the Bill’s general scheme finally published, but it may never be enacted [37].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, exogenous shocks are required to trigger a paradigm shift. Butler (2009) suggests that the economic recession triggered by the 2008 banking crisis could precipitate a move from hierarchy toward more epistemic learning in this case. …”
Section: Imposed Knowledge Usementioning
confidence: 94%
“…Hawkins [23] claims that alcohol related harm policies have failed implementations in the UK. Government seem to have concluded that people in the UK are aware of the side effects of drinking by emphasizing that in the sovereign nation citizens choose what is better for their own health and wellbeing [20]. It is obvious that policy advocates of public health practitioners differ from those of industry actors [24].…”
Section: Minimum Unit Price (Mup) Interventionmentioning
confidence: 99%